1D/2D TiO2/MoS2 Hybrid Nanostructures for Enhanced Photocatalytic CO2 Reduction. Issue 23 (21st October 2018) - Xu, Feiyan; Zhu, Bicheng; Cheng, Bei; Yu, Jiaguo; Xu, Jingsan
Abstract: Photocatalytic reduction of CO2 into solar fuels is recognized an attractive approach to solve the environmental and energy crisis. MoS2, a type of 2D transition metal dichalcogenides, has attracted significant attention in photoelectronics, sensors and photo/electrocatalytic water splitting owing to its remarkable properties. Nevertheless, to date, MoS2 is barely used as (co)catalyst for CO2 photoreduction. Herein, novel 1D/2D TiO2 /MoS2 nanostructured hybrid with TiO2 fibers covered by MoS2 nanosheets by hydrothermal transformation method is fabricated. The MoS2 sheet arrays show a lateral size of ≈80 nm and a thickness of down to 2 nm, vertically and uniformly standing upon the TiO2 fibers. X‐ray photoelectron spectroscopy (XPS) results and density functional theory (DFT) calculation imply the intimate chemical interaction between MoS2 and TiO2 upon hybridization, which can facilitate electron–hole separation upon photoexcitation. In addition, the hierarchical TiO2 /MoS2 nanostructure shows enhanced optical absorption and CO2 adsorption, therefore, a superior photocatalytic activity for reducing CO2 into methane and methanol is achieved over the hybrid as compared to pristine TiO2 . Isotope ( 13 C) tracer test confirms that the products are produced from the photocatalytic reduction of the CO2 source instead of any organic contaminants. This work offers an alternative approach to rationally design and synthesize TiO2 ‐based photocatalysts toward high‐efficiency photoreduction of CO2 . Abstract : A novel 1D/2D TiO2 /MoS2 hybrid nanostructure is hydrothermally synthesized by growing MoS2 nanosheets vertically on the electrospun TiO2 nanofiber. Such hybrid nanofiber exhibits an enhanced photocatalytic activity toward the reduction of CO2 into CH4 and CH3 OH under UV–visible light irradiation due to the enhanced light absorption and CO2 adsorption and the efficient charge carrier separation.